Man as a debtor: Introduction to the problem - Asafaylo, Marina P. (Opción, 2020)
The article refers to a concept that is central to the ancient Indian religious and mythological worldview: dharma, which is directly related to the idea of man as debtor is done through a comparative method of qualitative research. As a result, the state of indebtedness obtained since birth is revealed to man through the system of duties at different stages of life. In conclusion, each Varna must carry out a strictly defined circle of duties, ensuring the functioning of society in general. Dharma as debt is also found in the doctrine of the three goals of life (Trivarga)